1999
DOI: 10.1046/j.1365-2621.1999.00262.x
|View full text |Cite
|
Sign up to set email alerts
|

Application of native and phosphorylated tapioca starches in potato starch noodle

Abstract: Summary Characteristics of potato starch noodles substituted with native, phosphorylated and commercial phosphorylated (MTS283) tapioca starches were evaluated. Substitution of up to 17% with phosphorylated tapioca starch or up to 35% with MTS283 improved the quality of potato starch noodles. The resulting noodles were transparent and less brittle when uncooked, and were moderately elastic, less sticky and experienced lower cooking loss and less swelling when cooked. Substitution with native tapioca starch of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 6 publications
0
15
0
1
Order By: Relevance
“…Starch noodles should also have a short cooking time with little loss of solid in the cooking water (Galvez & Resurrection, 1992). It was recently demonstrated that starch noodle quality has three distinct aspects: sensory property (appearance of dry starch noodles), cooking property (eating quality) and texture property of cooked starch noodles (Baek, Cha, & Lim, 2001;Chen et al, 2002;Collado & Corke, 1997;Collado et al, 2001;Kaur, Singh, & Singh, 2005;Lee et al, 2005;Muhammad et al, 1999;Tam et al, 2004;Tan, 2007).…”
Section: Quality Evaluating Of Starch Noodlesmentioning
confidence: 99%
See 2 more Smart Citations
“…Starch noodles should also have a short cooking time with little loss of solid in the cooking water (Galvez & Resurrection, 1992). It was recently demonstrated that starch noodle quality has three distinct aspects: sensory property (appearance of dry starch noodles), cooking property (eating quality) and texture property of cooked starch noodles (Baek, Cha, & Lim, 2001;Chen et al, 2002;Collado & Corke, 1997;Collado et al, 2001;Kaur, Singh, & Singh, 2005;Lee et al, 2005;Muhammad et al, 1999;Tam et al, 2004;Tan, 2007).…”
Section: Quality Evaluating Of Starch Noodlesmentioning
confidence: 99%
“…Noodles were evaluated in sets of five samples per plate and each set was replicated twice; scores of each characteristic were averaged. Muhammad et al (1999) arranged 20 trained panelists to evaluate the elasticity, stickiness and taste of cooked noodles. Noodles were cooked in 200 mL of boiling distilled water for 1 min, drained for 30 s, cooled for 2 min, and were served to the panelists in 3-4 g portions.…”
Section: Sensory Propertymentioning
confidence: 99%
See 1 more Smart Citation
“…It originates from China and dates from at least 400 years ago (Cheng, 1985). Traditionally, mung bean starch is considered to be the most suitable raw material for starch noodle making, and the mung bean starch noodle is, consequently, regarded as the best of all kinds of starch noodles (Muhammad, Kusnandar, Hashim, & Rahman, 1999;Kasemsuwan et al, 1998). The high quality using mung bean starch probably results from its high amylase content.…”
Section: Introductionmentioning
confidence: 99%
“…It originates from China and dates at least 400 years ago (Cheng, 1985). Traditionally, mung bean starch is considered to be the most suitable raw material for starch noodle making, and the mung bean starch noodle is usually regarded as the best of all kinds of starch noodles (Kasemsuwan et al, 1998;Muhammad, Kusnandar, Hashim, & Rahman, 1999). The high quality of mung bean starch probably results from its high amylase content.…”
Section: Introductionmentioning
confidence: 99%